Materials on the Lepidoptera fauna of “Ecoportal de Piedra” National Park (Jujuy Province, North-Western Argentina). Part I. Pterophoridae (Lepidoptera: Pterophoridae) - Ustjuzhanin, P. Ya.; Kovtunovich, V. N.; Yakovlev, R. V.; Streltzov, A. N. (SHILAP Revista de lepidopterología, 2021)
Basing on the materials from Russian entomological expedition to Jujuy Province, North-Western Argentina, the participants of which were working in Ecoportal de Piedra National Park, 22 Pterophoridae species have been revealed, two of which, Emmelina doroshkini Ustjuzhanin & Kovtunovich sp. n. and E. reshetnikovi Ustjuzhanin & Kovtunovich sp. n., turned to be new to Science. Six more species, Bipunctiphorus nigroapicalis (Landry & Gielis, 1992), Stenoptilodes brevipennis (Zeller, 1874), S. taprobanes (Felder & Rogenhofer, 1875), Lioptilodes cuzcoicus Gielis, 1996, Adaina zephyria Barnes & Lindsey, 1921, and Hellinsia mauleicus (Gielis, 1991) have been indicated for Argentina for the first time, and eleven more species, Postplatyptilia flinti Gielis, 1991, Stenoptilodes sematodactyla (Berg, 1885), Lioptilodes aguilaicus Gielis, 1991, Oidaematophorus pseudotrachyphloeus Gielis, 2011, Singularia carabayus (Arenberger, 1990), Hellinsia angulofuscus (Gielis, 1991), H. chalupi Gielis, 2013, H. grandaevus (Meyrick, 1931), and H. tacanasensis Gielis, 2013 have been indicated for Jujuy Province for the first time. One species of the genus Singularia has not been identified on a unique female.